Study on Electron Tunneling Lifetime by Projected Green’s Function Approach in Single Quantum Well Semiconductor - Yanoar Pribadi Sarwono; Rui-Qin Zhang; Gagus Ketut Sunnardianto (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2023)
The tunnelling lifetime of an electron in a single quantum well subject to an externally applied electric field is calculated using the Projected Green’s Function (PGF) approach. The lifetime in the biased single well decreases as a function of the electric field in good agreement with the previous result. The tunnelling lifetime is revealed with the behavior of the ground-state shift and the wave amplitude in the first well. As the electric field increases, the ground state energy shifts, leading to lessened constructive interference between the initial and reflected electron waves. Consequently, the study is essential to characterize the performance of high-speed quantum devices.